ANALISIS FILM ANIMASI UPIN DAN IPIN DALAM PENERAPAN PROKES MELALUI PERILAKU HIDUP BERSIH DAN SEHAT - Norma Yanti; Mei Fita Asri Untari; Rofian (STKIP Subang, 2023)
This research was motivated by the implementation of health protocols through clean and healthy living behaviors of children at SDN Karangasem which have not been maximized. The focus of this study is how the analysis of the upin and Ipin episode 16 animated film